Evaluation of fecal microorganisms of children with cleft palate before and after palatoplasty - Vieira, Narciso Almeida; Borgo, Hilton Coimbra; Dalben, Gisele Da Silva; Bachega, Maria Irene; Pereira, Paulo Câmara Marques [UNESP] (FapUNIFESP (SciELO), 2013)
This study isolated and quantified intestinal bacteria of children with cleft palate before and after palatoplasty. A prospective study was conducted from May 2007 to September 2008 on 18 children with cleft palate, aged one to four years, of both genders, attending a tertiary cleft center in Brazil for palatoplasty, to analyze the effect of surgical palate repair on the concentration of anaerobes Bacteroides sp, Bifidobacterium sp and microaerophiles Lactobacillus sp in feces of infants with cleft palate before and 24 hours after treatment with cefazolin for palatoplasty. There was significant reduction of Lactobacillus sp (p < 0.002), Bacteroides sp (p < 0.001) and Bifidobacterium sp (p = 0.021) after palatoplasty, revealing that surgery and utilization of cefazolin significantly influenced the fecal microbiota comparing collections before and after surgery. However, due to study limitations, it was not possible to conclude that other isolated factors, such as surgical stress, anesthetics and other medications used in palatoplasty might have a significant influence on the microbiota. Considering the important participation of the intestinal microbiota on both local and systemic metabolic and immunological activities of the host, professionals should be attentive to the possible influence of these changes in patients submitted to cleft repair. © 2013, Sociedade Brasileira de Microbiologia.
Keywords: Cleft palate; Cleft palate/surgery; Environmental microbiology; Feces; Surgery/plastic